Management Training to Improve the Effectiveness of Student Development at Mahad Tahfidz Darul Falah, Selangor, Malaysia - Solechan, Solechan; Sintasari, Beny; Azizah, Mar’atul; Kartiko, Ari; Hakim, Agisni Fadlan Abdul; Liani, Astri (An Naf'ah: Jurnal Pengabdian Masyarakat, 2025)
This community service was carried out at Ma'had Tahfidz Darul Falah, Selangor, Malaysia, involving 15 core administrators of Ma'had using a participatory-educational approach. The community service activities were divided into three stages, namely the preparation stage and identification of needs through field observation and interviews. The implementation stage of training in the form of a three-day intensive workshop that integrated interactive lecture methods, group discussions, case studies, and simulations of organizational structure preparation and annual work program planning as well as the evaluation and follow-up stage in the form of evaluation. The results of the community service showed improvements in the managerial awareness of administrators, a more systematic organizational structure arrangement, increased communication and coordination between administrators, and more structured and sustainable program planning. The contribution of this community service lies in the development of Islamic education management science, especially in the context of traditional religious institutions that still rely on informal systems, by presenting a managerial training model based on local practices and a participatory approach that can be adopted by similar institutions in an effort to increase organizational effectiveness and santri development